Enhancement of English Student Learning Results through Total Physical Response (TPR) Method - Wahyuni Sakka; Muhammad Aswad; Fajriani Fajriani (EDUVELOP, 2018)
The study was conducted in Madrasah Tsanawiah (MTs) Totolisi Sendana Majene Distric, West Sulawesi Province, this school was chosen purposively based on several considerations, namely: 1) the lack of number of English teachers, 2) the minimum number of learners is proportional to their interest in learning English, 3) the methods used by educators are less creative and innovative. Based on the issues raised in this study, the research entitled "The Effect of TPR (Total Physical Response) Method on Improving Learning Outcomes through Story Telling Activity English" is a method of Quasi Experimental Design research which in this study using a model that is two groups pretest-posttest design. The research design used in this study is a research model conducted by involving a comparison group ". Thus the treatment results can be known more accurately, because it can compare with the situation before being treated and compare methods applied by the English teacher. Based on the descriptions, it can be concluded that There is an influence between the learning value of English learners at the time before and after the implementation of TPR method of Total Physical Response) through story telling activity to students of Madrasah Tsanawiah (MTs) Totolisi Sendana Majene district. There is an increase in the average value in the experimental group that has the average value of pre-test of 47.26 after being given treatment in the form of application of TPR method (Total Physical Response) through the activity of storytelling, the result of the value of English increases with the average value post-test of 68.44. While in the control group did not increase with the value in pre-test 44.62 while post-test 56.52.